Experimental investigation of nonlinear springing and fatigue assessment of a 308, 000 DWT oil tanker and a 205, 000 DWT bulk carrier in a basin. (1st December 2020) - Yang, Peng; Zhang, Wei; Ding, Jun; Gu, Xuekang; Chen, Haosen
Abstract: In the IACS harmonized common structural rules, it is hoped that the fatigue damage to ship structures caused by springing can be rationally analysed. In the case of limited resources in a basin, it is impossible to carry out model tests of wave-induced vibrations for many short-term sea states. Based on wave load transfer function under regular waves, a simplified method is established to evaluate the nonlinear springing and fatigue damage to ship structures under many different short-term and long-term sea states and is proposed by using wave loads of wave-frequency and high-frequency components. The wave loading model tests of a 308, 000 DWT VLCC (very large crude container) and a 205, 000 DWT VLBC (very large bulk carrier) are carried out; moreover, the springing influence on structural fatigue is assessed in short-term sea states by using stress data measured from model tests. Furthermore, the springing influence on structural fatigue is studied in long-term sea states for some typical sea routes. It is concluded that the impact of springing is obvious on a VLCC and VLBC under ballast conditions and differs for various routes. The simplified method can assess the fatigue damage due to springing properly. Highlights: A simplified method is proposed to calculate nonlinear wave-induced vibrations based on load transfer functions in regular waves. The ten-segmented model tests of a 308, 000 DWT very large crude carrier and a 205, 000 DWT bulk carrier are carried out in tower tank. The ratios of fatigue damage between considering springing and without springing are respectively 1.37 2.45 and 1.21 1.52 for the VLCC and the VLBC.